Pengkajian Kemampuan Siswa dalam Menggambarkan Konsep Matematika Melalui Metode Pembelajaran Matematika Realistik yang Mengadopsi Prinsip Etnomatematika - Arga Adriansah; Fitania Safitri; Adhitya Ardhana Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to examine students' abilities in describing mathematical concepts through Realistic Mathematics learning methods that adopt Ethnomathematics principles. This method encourages students to understand mathematical concepts through real-world situations that are relevant to their culture and context. The research was conducted using qualitative and quantitative approaches in a secondary school in Indonesia. Data was collected through classroom observations, interviews with teachers and students, as well as analysis of test results and student assignments. The research results show that the use of Realistic Mathematics Learning Methods that integrate Ethnomathematics principles can significantly improve students' abilities in describing and applying mathematical concepts in the context of everyday life related to their culture. The implication of this research is the importance of integrating cultural aspects in mathematics learning to increase student engagement and understanding of the subject.